2012
DOI: 10.1097/ta.0b013e31825a785a
|View full text |Cite
|
Sign up to set email alerts
|

Is the sympathetic system involved in shock-induced gut and lung injury?

Abstract: BACKGROUND β-blockade (BB) has been shown to prevent bone marrow (BM) dysfunction after trauma and hemorrhagic shock (HS). The impact of the sympathetic system and the role of BB on shock-induced distant organ injury is not known. This study will determine if BB has systemic effects and can diminish gut and lung injury after trauma and HS. METHODS Male Sprague-Dawley rats were subjected to lung contusion (LC) followed by 45 minute of HS. Animals (n = 6 per group) were then randomized to either receive propra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…However, plasma from LCHS + β2B or LCHS + β3B animals improved BM HPC colony growth, suggesting that both β2B and β3B have protective systemic effects. Baranski et al 18 showed similar improvement in HPC colony growth with LCHS plasma of animals given with propranolol.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, plasma from LCHS + β2B or LCHS + β3B animals improved BM HPC colony growth, suggesting that both β2B and β3B have protective systemic effects. Baranski et al 18 showed similar improvement in HPC colony growth with LCHS plasma of animals given with propranolol.…”
Section: Discussionmentioning
confidence: 81%
“…3,18 While HPC mobilization and homing play a role in tissue repair at the sites of injury, 2 an excessive release of HPCs with a corresponding decrease in BM cellularity may contribute to persistent BM dysfunction. In this study, when β2B and β3B were administered after LCHS, there was a significant increase in BM cellularity after 3 hours, and this protection of BM cellularity was maintained at 7 days after injury.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of norepinephrine are protective from lung injury but maybe contribute to the generalized immunosuppression in severe trauma. Meanwhile, Beta-blockade of propranolol can protect against the detrimental effects of trauma on lungs by blunting the exaggerated sympathetic response after shock and injury 83 . Also, the activation of adrenergic receptors and releasing of CA play an important role in traumatic infections 84 , 85 .…”
Section: The Dynamic Regularity Of Neuroendocrine Immune Network In Tmentioning
confidence: 99%
“…(82) In a rodent model of lung contusion and hemorrhagic shock with and without propranolol administration, lung injury scores were significantly attenuated three hours after injury in the propranolol treatment group. (83) Baranski et al hypothesized that the improvement in lung injury scores was related to either the systemic effects of propranolol or a reduction in gut permeability. (83) …”
Section: Pulmonary Dysfunctionmentioning
confidence: 99%
“…(83) Baranski et al hypothesized that the improvement in lung injury scores was related to either the systemic effects of propranolol or a reduction in gut permeability. (83) …”
Section: Pulmonary Dysfunctionmentioning
confidence: 99%